2009
DOI: 10.1002/uog.7356
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and potential limitations of transvaginal sonography for bladder endometriosis

Abstract: Objectives (70.6% vs. 25.0%; P = 0.005). At TVS, the nodule was hypoechogenic, its morphology was either elongated ('comma-shaped': 12/18, 66.7%) or spherical (6/18, 33.3%), and the site involved was the dome (11/18, 61.1%) or the base (7/18, 38.9%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 18 publications
3
59
1
2
Order By: Relevance
“…From this point of view, our results are consistent with the results of Savelli et al [9] which reported a sensitivity of 44% of gel SVG in the diagnosis of vesical endometriosis.…”
Section: Discussionsupporting
confidence: 93%
“…From this point of view, our results are consistent with the results of Savelli et al [9] which reported a sensitivity of 44% of gel SVG in the diagnosis of vesical endometriosis.…”
Section: Discussionsupporting
confidence: 93%
“…It is thought to occur in approximately 1-2% of patients with endometriosis and involves the bladder in 90% of these cases. 18,21 Bladder endometriosis can be described as superficial or deep depending on the degree of invasion. Deep bladder endometriosis involves invasion of the muscular is and symptoms can include dysuria, frequency, nocturia, bladder spasms, suprapubic pain and haematuria.…”
Section: Bladder and Ureteric Endometriosismentioning
confidence: 99%
“…Deep bladder endometriosis involves invasion of the muscular is and symptoms can include dysuria, frequency, nocturia, bladder spasms, suprapubic pain and haematuria. 18 Superficial endometriosis describes endometriosis on the peritoneal surface overlying the bladder.…”
Section: Bladder and Ureteric Endometriosismentioning
confidence: 99%
See 2 more Smart Citations